Volumetric Analysis Of Benzene Vapor Adsorption On Lilsx Zeolite İn A High Vacuum Adsorption Device - Rakhmatkarieva Firuza Gayratovna, Abdurakhmonov Eldor Baratovich Yakubov Yuldosh Yusupboevich (International Journal of Advanced Science and Technology, 2020)
The study of molecules adsorption of different geometric and electronic structure by zeolites of different composition and structure is of great interest to study the effect on the adsorption of chemical nature of adsorbents surface. Zeolites are porous crystals, so the micropore structure of zeolites is determined with high accuracy, their adsorption properties are physical-chemical constants, which can be calculated theoretically based on the calculation of the potential interaction energy adsorbate-adsorbate and adsorbate-adsorbent in zeolites. These data are of great interest for the development of the theory of adsorption forces and intermolecular interactions. However, the calculation of the potential energy of adsorption is difficult due to the complexity of the crystal structure and the potential field in the zeolite channels. The high benzene content degrades the environmental and technological properties of fuels. To select a highly efficient sorbent for dearomatization of fuel, studies of regularities of benzene adsorption in various zeolites are necessary. The isotherm, differential heats, and thermokinetics of benzene adsorption in LiLSX zeolite at 303K were measured using the adsorption calorimetry method. The differential molar entropy and free adsorption energy are calculated. The adsorption isotherm is completely described by the three-term equation of VMOT. The average molar integral entropy of benzene adsorption in zeolite LiLSX is - 89,22 J/mol*K, which indicates the localization of benzene molecules in LiLSX zeolite.